2018
DOI: 10.1038/s41390-018-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood curiosity and kindergarten reading and math academic achievement

Abstract: BACKGROUND Although children’s curiosity is thought to be important for early learning, the association of curiosity with early academic achievement has not been tested. We hypothesized that greater curiosity would be associated with greater kindergarten academic achievement in reading and math. METHODS Sample included 6200 children in the Early Childhood Longitudinal Study, Birth Cohort. Measures at kindergarten included direct assessments of reading and math, and a parent-report behavioral questionnaire fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 45 publications
2
69
0
3
Order By: Relevance
“…Second, soft skills foster the development of cognitive abilities that further boost learning (Cunha & Heckman, 2007). Research has shown that children who are more motivated and curious tend to learn more and perform better in standardized tests (Heckman & Kautz, 2012;Shah, Weeks, Richards, & Kaciroti, 2018). Not surprisingly, soft skills predict success later in life as just as strongly as cognitive abilities (Kautz, Heckman, Diris, Ter Weel, & Borghans, 2014).…”
Section: Growing Importance Of Soft Skillsmentioning
confidence: 99%
“…Second, soft skills foster the development of cognitive abilities that further boost learning (Cunha & Heckman, 2007). Research has shown that children who are more motivated and curious tend to learn more and perform better in standardized tests (Heckman & Kautz, 2012;Shah, Weeks, Richards, & Kaciroti, 2018). Not surprisingly, soft skills predict success later in life as just as strongly as cognitive abilities (Kautz, Heckman, Diris, Ter Weel, & Borghans, 2014).…”
Section: Growing Importance Of Soft Skillsmentioning
confidence: 99%
“…Curiosity is the desire to acquire new knowledge and experiences. It has also been described as a motivation for exploratory behavior and for seeking answers to what is unknown [27]. Researchers often place curiosity within the broader category of information-seeking exploratory behavior, with curiosity being a special form that is internally motivated, whereas the broader term refers to a drive that can be intrinsic or extrinsic [28].…”
Section: Curiositymentioning
confidence: 99%
“…Through curiosity, initiative, and persistence, children become primary agents in their own learning, becoming skilled in observing the world in expansive ways, formulating meaningful questions, and discovering their own answers [24]. Additionally, curiosity is associated with greater kindergarten reading and math achievement, and accordingly is highlighted among academic and even pediatric guidelines as a foundation for early learning [27].…”
Section: Curiositymentioning
confidence: 99%
“…Other work also showed that people are generally motivated to seek information even if it entails mental and physical costs (Hsee, & Ruan, 2016). The feeling of curiosity has also been considered as an initial precursor of the more developed and individualized interest (Renninger & Hidi, 2016), and indeed, researchers have shown the beneficial effects of curiosity in applied settings such education and work places (Reio & Callahan, 2004;Shah, Weeks, Richards, & Kaciroti, 2018).…”
Section: Curiosity Carry-over Effectmentioning
confidence: 99%